Evaluation of heat transfer performance of a channel mounted with square-wing perforated V-type baffles - Eiamsa-Ard, Smith; Phila, Arnut; Thianpong, Chinaruk; Chuwattanakul, Varesa; Maruyama, Naoki; Hirota, Masafumi (My University, 2025)
The current study examines the aerothermal performance behaviors of a rectangular-channel with square-wing perforated V-type baffles (SW-PVBs). The SW-PVBs were attached to lower channel walls at five attack angles, θ = 0° (solid V-type baffle), 22.5°, 45°, 67.5° and 90°. The heat transfer and pressure drop results of a channel without SW-PVBs were performed to normalize the results of the SW-PVBs and evaluate thermal performance factors (TPFs). It can be observed that as the attack angles decreased, the heat transfer and pressure loss rose. Among the SW-PVBs that were tested, those characterized by θ = 22.5° exhibited the most significant improvement in heat transfer, whereas SW-PVBs with θ = 45° gave the highest thermal performance factors. Additionally, the SW-PVBs with θ = 45° offered the highest TPF, as high as 1.93.
Keywords: Baffle; heat exchanger channel; heat transfer augmentation; square-wing perforated V-type baffles; thermal performance